The nature and age incidence of flat-footedness among Stellenbosch school girls, and the improvement with corrective foot exercises of the height of the longitudinal arch of the foot - Lubbe, Hester A.(Hester Aletta) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed. Ph.) -- University of Stellenbosch, 1944.